UJI VALIDITAS PENGEMBANGAN LEMBAR KERJA SISWA MATEMATIKA BERBASIS KONSTRUKTIVISME PADA MATERI PROGRAM LINEAR - Puji Rahayu; Putri Inayati (Prodi Pendidikan Matematika Universitas PGRI Ronggolawe, 2020)
The purpose of this research is to produce a valid LKS. This development research uses the Four-D model which consists of four stages, namely: a) define, b) design and c) develop and d) disseminate. But in this study only arrived at the development stage by testing the validity. The research instrument used in constructivism-based LKS was in the form of validation sheets used to assess the validity of LKS. The results of the validity study of Student Worksheets (LKS) based on constructivism by material experts get the overall average score is 75.83% with good criteria, while the validation by media experts get an overall average score of 89.72% with very good criteria. Thus the results of this development research show that constructivism based LKS mathematics in the Program Linear material meet valid qualifications.